2011
DOI: 10.3382/ps.2011-01470
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analytical study of productive and nutritional interactions of mycotoxins in broilers

Abstract: A meta-analysis was carried out to study the association of mycotoxins with performance, productive indices, and organ weights in broilers. Ninety-eight papers published between 1980 and 2009 were used, totaling 1,401 diets and 37,371 animals. Meta-analysis followed 3 sequential analyses: graphical, correlation, and variance-covariance. The mycotoxin presence in diets reduced (P < 0.05) feed intake by 12% and weight gain by 14% compared with control group. Ochratoxins and aflatoxins were the mycotoxins with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 16 publications
7
41
1
1
Order By: Relevance
“…In the current study, however, DON levels of 10 mg/kg had a stronger inhibiting effect on the growth of chickens compared with 5 mg/kg, as weight differences were more pronounced between 5 and 10 mg/kg DON groups. These results are in agreement with previous studies, demonstrating that feeding of DON-contaminated diets compromised the growth performance of chickens (Dänicke et al 2003;Andretta et al 2011;Awad et al 2012b).…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, however, DON levels of 10 mg/kg had a stronger inhibiting effect on the growth of chickens compared with 5 mg/kg, as weight differences were more pronounced between 5 and 10 mg/kg DON groups. These results are in agreement with previous studies, demonstrating that feeding of DON-contaminated diets compromised the growth performance of chickens (Dänicke et al 2003;Andretta et al 2011;Awad et al 2012b).…”
Section: Discussionsupporting
confidence: 93%
“…The increased F/G in broilers fed AFB-contaminated diets (44.5 μg/kg) was observed by previous studies [26]. Others also observed negative effects of AFB (1 to 5 mg/kg) on growth performance in broilers [5][6][7]27]. On the contrary, low purified AFB 1 (50 μg/kg) did not affect growth performance in broilers [3].…”
Section: Growth Performancesupporting
confidence: 53%
“…The occurrence of AFB poses a great threat to broiler health because of its adverse effects on growth performance, immunity, intestinal morphology, blood profiles and hepatic functions [3][4][5][6]. A meta-analysis study indicated that AFB-contaminated diets caused 11% reduction in feed intake and daily weight gain in broilers, and the feed conversion ratio was also decreased by 6% [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxins are toxic secondary biomolecules produced by fungus or molds. However, different types of mycotoxins may be produced by one mold species, while the same mycotoxin may be produced by several species (Andretta et al, 2011). Hence, classification of mycotoxins can be made based on their chemical structures as well as reactive functional groups (e.g., primary/ secondary amines, carboxylic acids, hydroxyl (or phenolic) groups, lactams, and amides) (Grenier and Applegate, 2013).…”
Section: Mycotoxinsmentioning
confidence: 99%